Characterization of an Escherichia coli K-12 F-Con-mutant. - Havekes, L M (1976)
An Escherichia coli K-12 F-mutant defective in conjugation was isolated by means of a zygotic induction enrichment procedure. The recipient ability of the mutant was reduced about 50 times owing to a block in one of the first steps of the conjugation process. In the mutant, cell envelope alterations could not be observed. Sensitivity toward detergents, antibiotics, and phages was unaltered. The mutation appeared to be co-transducible with pyrD. The linkage order in the region of the mutation is origin KL 99-con-pyrD-aroA.